InfoQuest Information Delivery at UNL - Pearson, Debra; Zillig, Brian; Lewandowski, Sharon ([S.l.] : Distributed by ERIC Clearinghouse, 1997)
The University of Nebraska-Lincoln (UNL) Libraries designed and implemented a fast and efficient method of transferring materials between and among the UNL campuses for users of the UNL Libraries. The prior array of services were difficult to use and did not serve all patron types. That system relied upon student workers to retrieve and deliver materials. The new system was intended to include delivery service to the new Beadle Center for Genetics and Bio-Materials Research facility as well as to all the branch libraries. A survey was conducted of features found in existing services. The new service was designed to offer delivery to all user types, and to provide two deliveries per day, instead of one, to several branch libraries. A new electronic patron request form was created. Implementation of the new service appears successful, with desired improvements for both library staff and patrons. InfoQuest request forms and user policy statements are appended. (Author/SWC)
ERIC Note: Paper presented at the Annual Meeting of the Nebraska Library Association (Crete, NE, May 23, 1997).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academic Libraries; Access to Information; Computer Networks; Document Delivery; Higher Education; Information Retrieval; Interlibrary Loans; Library Automation; Library Services; Online Systems; User Needs (Information); University of Nebraska Lincoln; Customer Services; Reports, Descriptive; Speeches/Meeting Papers